Bulgaria : Staff Report for the 2000 Article IV Consultation and Fifth Review Under the Extended Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Bulgaria's currency board arrangement continues to have broad political and public support and shows no signs of strain, as interest rates are low and stable, fiscal reserves ample, and banks liquid. A structural reform agenda has also been implemented. The authorities have improved banking supervision, started the overhaul of the pension and health care systems, and liberalized trade and prices. Executive Directors stressed the need to strengthen the bank supervision and corporate governance to reduce the perceived risks of lending to the private sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet